Towards the eradication of poverty by enhancing existing technology and infractructure through technological awareness - Hanafi Ismail; Mohd. Ruddin Abdul Ghani; Abdullah Asuhaimi Mohd. Zin; Tharek Abdul Rahman, 1955-; Shamsudin Mohd. Amin; Harun Ismail; Mortaza Mohamed, 1957-; ASAIHL Seminar: Post Surabaya Pre Perth: Technology Overcoming Poverty: Higher Education's Contribution to Development (1991: UTM, KL)
12